Over‐expression of TNNI3K is associated with early‐stage carcinogenesis of cholangiocarcinoma. Issue 2 (8th November 2018) - Yeh, Chun‐Nan; Chen, Ming‐Huang; Chang, Yu‐Chan; Wu, Ren‐Chin; Tsao, Lee‐Cheng; Wang, Shang‐Yu; Cheng, Chi‐Tung; Chiang, Kun‐Chun; Chen, Tsung‐Wen; Hsiao, Michael; Weng, Wen‐Hui
Abstract : Cholangiocarcinoma (CCA) is a devastating disease with very poor prognosis due to late diagnosis and resistance to traditional chemotherapies and radiotherapies. Herein, thioacetamide (TAA)‐induced rat CCA model and CGCCA cell line were used; we aim to study the cytogenetic features during tumoral development of CCA and uncover the mystery regarding carcinogenesis of CCA. The Array comparative genomic hybridization analysis, in silico method, gene knockdown, Western blot, cell count proliferation assay, clonogenecity assay, and IHC staining were applied in this study. Array comparative genomic hybridization analysis was performed on all different TAA‐induced phases of rat tissues to reveal the certain pattern, +2q45, +Xq22, −12p12, have been identified for the tumor early stage, where involve the gene TNNI3K . In addition, 16 genes and 3 loci were associated with rapid tumor progression; JAK‐STAT signaling pathway was highly correlated to late stage of CCA. In silico database was used to observe TNNI3K was highly express at tumor part compared with normal adjacent tissue in CCA patients from TCGA dataset. Furthermore, the growth of TNNI3K ‐knockdown SNU308 and HuCCT1 cells decreased when compared with cells transfected with an empty vector cell demonstrated by proliferation and colonogenecity assay. Besides, over expression of TNNI3K was especially confirmed on human CCA tumors and compared with the intrahepatic duct stone bile duct tissues and normal bile duct tissues ( P  < 0.001). Our findings might uncover the mystery regarding carcinogenesis of CCA, and provide the potential genetic mechanism to the clinicians some ideas for the patients' treatment.